Brothers, Believers, Brave Mujahideen: Focusing Attention on the Audience of Violent Jihadist Preachers - Aly, Anne (Taylor & Francis, 2016)
© 2016 Taylor & Francis Group, LLC. The exponential growth in the use of the Internet and social media by terrorist actors and violent extremists has generated research interest into terrorism and the Internet. Much of this research is focused on the kinds of messages being spread via the various media platforms that host violent extremist content. This research has yielded significant insights into how organizations such as Al Qaeda and Islamic State craft their messages, the mediums they use to disseminate their messages, and the ways in which they reach their audiences. Yet we are still no closer to understanding why certain messaging appeals to certain people in certain ways and not to others. Within the literature on terrorism and the Internet, the audience—those individuals who receive messages, make meaning from them and then decide whether to act on them—is conspicuously missing. As a result, research into terrorism and the Internet can only hypothesize about the nature and extent of influence that terrorist messages wield. It is often based on an assumption that the violent extremist narrative works like a magic bullet to radicalize audiences already vulnerable and predisposed to becoming violent. Utilizing media theory approaches to studying the audience as an active agent in meaning-making, this article proposes a research framework for developing the current focus on terrorism and the Internet.